Push and Pull Factors behind Female Labor-force Participation Decision, a Study of Kerala and West Bengal: two States of India - Choudhury, Sayantani Roy (Journal of Social and Development Sciences, 2013)
This paper wants to show whether the decision of female labor force participation depends on economic factors or social factors. Female labor force participation is an outcome of both the factors. It can be possible that, economic and social factors play two different kinds of role. This paper tries to identify those push and pull factors and examine the significance of those factors in the decision regarding female labor force participation in two states of India, Kerala and West Bengal. Whether the factors are macroeconomic like SDP, literacy rate and urbanization, which can ’pull’ FLPR up, or, the factors are micro economic, personal, poverty, and insecurity, which can ’push’ the FLPR. By using binary logistic regression method, it is found in the paper that the micro level personal factors have more powerful influence on FLPR. The paper suggests that if we want to judge women’s development through the FLPR, first we search for the factors behind that high FLPR. If the underline factors are ’push factors’, the formula for GDI calculation should also be altered.